Study of 8-year-old children with a history of respiratory syncytial virus bronchiolitis in infancy. Issue 6104 (7th January 1978) - Sims, D G; Downham, M A; Gardner, P S; Webb, J K; Weightman, D
Abstract : Thirty-five children known to have had respiratory syncytial virus bronchiolitis in infancy were examined at the age of 8 and their respiratory function tested. The results were compared with those in 35 controls matched for age, sex, and social class. Although 18 of the children who had had bronchiolitis in infancy had experienced subsequent episodes of wheezing, these were neither severe nor frequent in most cases and had apparently ceased by the age of 8. Nevertheless, the mean exercise bronchial lability of the children who had had bronchiolitis was significantly higher than that of the control children and the mean peak expiratory flow rate at rest significantly lower. Atopy, assessed by family and personal history alone, did not seem to be related to either bronchiolitis or wheezing episodes after bronchiolitis. The parents of the children who had had bronchiolitis smoked significantly more cigarettes during the infant's first year of life than those of the control children. The results suggest that bronchiolitis and childhood asthma are not closely related. Bronchial hyperreactivity might be inherited independently of atopy, but environmental factors seem the most likely link between severe respiratory infection in infancy and chronic or recurrent respiratory illness in adult life.